Housing Systems Influence Gut Microbiota Composition of Sows but Not of Their Piglets - Kubasova, Tereza; Davidova-Gerzova, Lenka; Merlot, Elodie; Medvecky, Matej; Polansky, Ondrej; Gardan-Salmon, Delphine; Quesnel, Helene; Rychlik, Ivan (PloS one, 2017)
Different housing systems can be used in pig production and little is known about their effect on gut microbiota composition. In this study we characterized fecal microbiota by sequencing the rRNA genes in sows kept during gestation in conventional pens with a slatted floor and in enriched pens with a floor covered with deep straw. After farrowing, microbiota of 1- and 4-day-old piglets were also monitored. Microbiota of sows from the enriched system contained significantly more Prevotella, Parabacteroides, CF231, Phascolarctobacterium, Fibrobacter, Anaerovibrio and YRC22 and significantly less Lactobacillus, Bulleidia, Lachnospira, Dorea, Ruminococcus and Oscillospira than microbiota of sows from the conventional system. The Firmicutes to Bacteroidetes ratio was 0.96 in the microbiota of sows kept in the enriched pens and this increased to 1.66 in the microbiota of sows kept in the conventional system. The production system therefore influenced microbiota composition, most likely due the ingestion of the straw. The microbiota of 1- and 4-day-old piglets differed from the microbiota of sows and sows therefore did not represent the most important source for their colonization in early days of life.
Keywords: prasata; Behavior, Animal; Feces; Swine; Animals, Newborn; chov zvířat; mikrobiota; feces; Gastrointestinal Microbiome; Microbiota; novorozená zvířata; střevní mikroflóra; Animals; ženské pohlaví; zvířata; Animal Husbandry; chování zvířat; Female; Housing, Animal; bydlení zvířat